Sosialisasi Pembuatan Telur Pindang dengan Penambahan Bubuk Teh dan Lengkuas di Desa Aron Kecamatan Kuta Baro Kabupaten Aceh Besar - Chairil Anwar; Irhami, Irhami; Ika Rezvani Aprita; Endiyani, Endiyani; Sri Agustina; Maghfirah, Maghfirah; Mulla Kemalawaty; Irmayanti, Irmayanti (Universitas Methodist Indonesia, 2025)
Eggs are a type of food from poultry that is most consumed by the Indonesian people. Eggs for consumption are the most common eggs on the market. Egg scanning is a form of processing with a combination of certain herbs and boiling. Pindang eggs are a traditional egg processed product that uses protein tanning ingredients The activity was carried out in Aron village, Aceh Besar with the aim of introducing and socializing the use of tea powder and galangal as auxiliary ingredients that can be used in making pindang eggs. This service activity is carried out in several stages, namely counseling and socialization as well as training and assistance to the village community. The results of this service activity went smoothly and the community really appreciated this activity with a lot of public interest to participate and participate in this service activity. Many people are actively discussing and involved with the service team related to community empowerment through this training so that the community gets information and knowledge about the use of tea powder and galangal.